Blended Media Dapat Meningkatkan Motivasi Belajar Efektif dan Interaktif - Nur intan Cahyaningrum; Rosdiana (Jurnal Pendidikan UNIGA, 2026)
The rapid development of digital technology has brought significant changes to the field of education, particularly in the learning process. However, low student learning motivation remains a major challenge, largely due to the dominance of conventional teaching methods that tend to be monotonous and less interactive. This article aims to analyze the implementation of blended media based on interactive multimedia in enhancing effective and interactive learning motivation.This study employ saliteratur rereview methodby analyzing various national and international scholarly sources. The findings indicate that blended media, which combines face-to-face instruction with online learning supported by interactive media such as multimedia and animation, is able to increase students’learning motivation strengthen active engagement, and create a more flexible and meaningful learning experience. In addition, the application of blended media encourages learner autonomy, accommodates diverse learning styles, and improves overall learning effectiveness. The implications of blended media are not onlyexperienced by students but also by educators, whoare required to shifttheirroletoward becoming learning facilitators. Therefore, blended media represents an innovative learning strategy that is relevant to national education policies and the demands of the digital era in improving the quality of education. Keywords: blended learning, interactive multimedia, learning motivation, interactive and effective learning.